2018
DOI: 10.2495/eid180111
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Indicators in Forest Fragments From Urban Watersheds

Abstract: Accelerated urbanization in Brazil promoted the rapid growth of cities and, in most cases, was not based on adequate land use planning. The result was the intense fragmentation of the landscape, causing the destruction and fragmentation of forest habitats, which were restricted to small and isolated remnants. In this sense, the present study promoted an analysis of the environmental quality of vegetation fragments in the sub-basins of Ribeirão Anhumas, Campinas, São Paulo, Brazil by calculating and interpretin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Using these indicators, the Environmental Quality Index was calculated by summing the weighted values associated with the indicators, for each remnant and according to their classification (Table 2) and fragments [31].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using these indicators, the Environmental Quality Index was calculated by summing the weighted values associated with the indicators, for each remnant and according to their classification (Table 2) and fragments [31].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was identified that in the upper, Figure 5: Resultados relativos à distância do vizinho mais próximo e conectividade. middle and lower regions, respectively, 66.7%, 83.3% and 88.0% of the fragments present connectivity [31].…”
Section: Nuclear Areamentioning
confidence: 98%
See 3 more Smart Citations